Unveiling the Origins of Selective Oxidation in Single-Atom Catalysis via Co-N4-C Intensified Radical and Nonradical Pathways - Yang, Mengxue; Hou, Zexi; Zhang, Xin; Gao, Baoyu; Li, Yanwei; Shang, Yanan; Yue, Qinyan; Duan, Xiaoguang; Xu, Xing (Environmental science & technology, 2022)
Single-atom catalysts (SACs)-based peroxymonosulfate (PMS) systems are highly selective to the type of organic pollutants while the mechanisms remain ambiguous. In this work, we carried out experimental and theoretical investigations to reveal the origins of selectivity of radical and nonradical pathways in a designated Co-N4-C/PMS system. Two typical pollutants [bisphenol A (BPA) and metronidazole (MNZ)] with different molecular structures were employed for comparison. We found that radical oxidation (SO4•- and HO•) and nonradical electron-transfer pathway (ETP) co-existed in the Co-N4-C/PMS system. Pollutants (e.g., MNZ) with a high redox potential were degraded primarily by free radicals rather than ETP, while the oxidization of low-redox pollutants (e.g., BPA) was dominated by ETP at the surface region of Co-N4-C which overwhelmed the contributions of radicals in the homogeneous phase. Intriguingly, the contributions of radical and nonradical pathways could be manipulated by the PMS loading, which simultaneously increased the radical population and elevated the oxidation potential of Co-N4-C-PMS* complexes in ETP. Findings from this work will unravel the mysterious selective behavior of the SACs/PMS systems in the oxidation of different micropollutants.Single-atom catalysts (SACs)-based peroxymonosulfate (PMS) systems are highly selective to the type of organic pollutants while the mechanisms remain ambiguous. In this work, we carried out experimental and theoretical investigations to reveal the origins of selectivity of radical and nonradical pathways in a designated Co-N4-C/PMS system. Two typical pollutants [bisphenol A (BPA) and metronidazole (MNZ)] with different molecular structures were employed for comparison. We found that radical oxidation (SO4•- and HO•) and nonradical electron-transfer pathway (ETP) co-existed in the Co-N4-C/PMS system. Pollutants (e.g., MNZ) with a high redox potential were degraded primarily by free radicals rather than ETP, while the oxidization of low-redox pollutants (e.g., BPA) was dominated by ETP at the surface region of Co-N4-C which overwhelmed the contributions of radicals in the homogeneous phase. Intriguingly, the contributions of radical and nonradical pathways could be manipulated by the PMS loading, which simultaneously increased the radical population and elevated the oxidation potential of Co-N4-C-PMS* complexes in ETP. Findings from this work will unravel the mysterious selective behavior of the SACs/PMS systems in the oxidation of different micropollutants.